A STUDY ON LEADERSHIP DEVELOPMENT ON FORMAL PROGRAMMES AND POLICIES OF AN ORGANIZATION - RAO, K. VENKATA; SUCHARITHA, Dr. D. (IJRDO - Journal of Social Science and Humanities Research, 2018)
In this article I review recent trends in leadership development arguing that much of the current growth is driven by financial, political and market pressures, to the relative neglect of philosophical and pedagogical perspectives on the nature and purpose of management, leadership within contemporary society. Whilst there is a general shift from formalised programmes towards flexible, experiential and customised provision, it seems that insufficient attention remains directed towards individual and organisational needs and requirements. Thus, for example, the majority of provision remains focused on the development of ‘leaders’ rather than the contextually embedded and collective processes of ‘leadership’. Finally, they highlight how individuals and organizations vary in their approachto and support for leadership development, and how these differences explain variation in leadership development processes and outcomes.